Efficacy of Inhaled Steroid Over Systemic Steroid in Stabilizing Acute Asthma in Emergency Room - B.V. Siva Vara Prasad Rao; Santhosh K B; Anil Sankol S M (National Board of Examinations Journal of Medical Sciences, 2025)
Background: Acute exacerbation of asthma is one of the most common illnesses presenting to Emergency Department. Glucocorticoids are good anti-inflammatory agents, effective at treating asthma and decreasing inflammation of the airways. Although systemic use of steroids is commonly being used, inhaled steroids could be also beneficial in acute asthma. AIM: To compare the efficacy of inhaled corticosteroid over systemic steroid in acute asthma. Materials & Methods: This was randomized, prospective, comparative study done on a total of 48patients in Emergency Department and ICU. All patients were assigned in random consecutive case fashion to one of the three groups such as Group I(inhaled steroid), Group II(intravenous steroid) and Group III(inhaled beta-2 agonist). The changes in respiratory rate, heart rate, oxygen saturation, peak expiratory flow and pulmonary score were recorded at 30minutes, 60minutes and 120minutes after treatment and were analysed. Results: Out of 48patients, highest number (n=13)(26.5%) of patients were of aged 30-39years and lowest being(n=2)(4.1%) aged 10-19years. There was female preponderance (n=21)(56.3%). Breathlessness grades were Grades 0 and 1(0%), Grade 2(n=13)(27.1%), Grade 3(n=26)(54.2%) and Grade 4(n=9)(18.7 %). Wheeze was present in 46(95.8%) patients. Accessory muscles of respiration were used in 34(70.8%) patients. There was no statistical difference (p>0.05) in decrease in respiratory rate, decrease in heart rate, increase in oxygen saturation, increase in peak flow and decrease in pulmonary score among all 3groups. Conclusion: The use of inhaled steroids is an effective treatment approach with faster clinical improvement compared to intravenous steroids in managing acute exacerbation of bronchial asthma in emergency room.